KUALITAS PELAYANAN PERUSAHAAN UMUM DAERAH (PERUMDA) GIRI TIRTA: STUDI DI KECAMATAN MANYAR KABUPATEN GRESIK - Anisya Naharuddin; Agus Widiyarta (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to analyze the quality of service in the Giri Tirta Regional Public Company of Gresik Regency using the SERVQUAL approach, which includes five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. This study uses a descriptive quantitative method with data obtained through questionnaire surveys filled out by customers. The SERVQUAL analysis was carried out to measure the gap between customer perception and service expectations. Study results show that the dimensions of Tangibles and Reliability have a positive gap, indicating that the physical facilities and service reliability are quite satisfactory. In contrast, the Responsiveness and Empathy dimensions show a negative gap, indicating the need to improve the speed of response to complaints and attention to customer needs. The Assurance dimension recorded a gap of zero, which suggests that the service is in line with expectations without more advantages. Improvements to dimensions with negative gaps are expected to improve overall service quality and customer satisfaction.